Population, Social Organization And Behaviors Of Macaca Fascicularis In Penang Botanical Gardens Penang, Malaysia - Karimullah, Karimullah (2011)

(untitled)
The population, social organization, general behaviours and mating behaviours of the species Macaca fascicularis have not been studied extensively previously in Penang, Malaysia. Thus this study was conducted on 1134 animals in 2007 in the Penang Botanical Gardens to consolidate these parameters. The major focus of the work was on the daily activity budgets, in terms of scan and focal sampling during all the months in the study, Of the daily activity budget, moving (15%) was found out to be the most frequent activity,